قرآنی احکامات و منہیات کا دائرہ کار: سورۃ الانفال کی روشنی میں عصری معنویت - Abdullah; Abdul Samad (الآفاق اسلامی و تحقیقی مجلہ)
The primary objective of the Qur’anic teachings is to align both individual and collective human life with divine guidance rooted in human nature (fiṭrah). The commands (aḥkām) of the Qur’an are divine instructions intended to guide humanity toward righteousness, while the prohibitions (manāhī) are designed to protect individuals and societies from harm. These commands and prohibitions were practically manifested during the life of the Prophet Muhammad (peace be upon him) and continue to hold relevance in today’s world. Surah al-Anfāl is a Madinan chapter primarily focused on the internal and external organization of the Muslim community. It discusses themes such as warfare, peace, obedience to the Prophet, the distribution of war booty, and unity among believers. The chapter not only outlines the rulings of combat and strategy but also emphasizes discipline, ethics, and the structure of an Islamic state.